Juridical Accountability of Railway Operators for Sexual Harassment on Commuter Trains: A Consumer Protection Perspective in the Jabodetabek Area - Ria Safitri; Kamilania (UIN Syarif Hidayatullah Jakarta, 2025)
This study examines the legal settlement of sexual harassment cases on Electric Rail Trains (KRL) in the Jabodetabek area by focusing on the juridical responsibility of PT Kereta Commuter Indonesia as a public transportation service provider from a consumer protection perspective. This research employs a normative juridical method with a qualitative approach, analyzing statutory regulations, particularly Law No. 12 of 2022 on Sexual Violence Crimes, Law No. 8 of 1999 on Consumer Protection, and railway service regulations. The study finds that although PT Kereta Commuter Indonesia has implemented various preventive measures, such as women-only carriages, surveillance systems, and reporting mechanisms, these efforts are not accompanied by compensatory accountability for victims. In practice, victims of sexual harassment do not receive restitution, compensation, or health assistance, either from perpetrators or from the service provider, as mandated under Article 19 of the Consumer Protection Law. This research argues that sexual harassment on public transportation should not be viewed solely as a criminal offense but also as a violation of consumer rights that triggers the liability of business actors.